Innovative Management in Subcontracting Business in Growing and Stagnating Economies - Karl-Heinz SCHMIDT (Revista de Management Comparat International)
The worldwide economic recession demonstrates: innovations are needed to increase productivity and competitivity of enterprises, especially of subcontracting companies. The paper compares the subcontracting business at a boom- and recessionphase, mainly in Japan and Germany. For Japan the components of subcontracting systems are exposed by a static and dynamic view. Changes of subcontracting firms from dependent, but stable suppliers of parts and services to extremely dependent subcontractors are shown for Japan. European subcontracting companies are found being less dependent, or even independent, networking suppliers. The worldwide dynamic view demonstrates: innovative management enables SMEs of former LDCs to compete with subcontracting companies of developed countries. The economic recession, yet, endangers the stability of the subcontracting systems worldwide.